(untitled) (Journal of Enam Medical College, 2021)
Background: Vitamin D deficiency is widespread among the children worldwide. Most of the third world countries have the high prevalence of vitamin D deficiency, especially among the children. Unfortunately very less research work has been conducted on this subject and Bangladesh is no exception to this. Vitamin D deficiency among the Bangladeshi children has not been investigated at a level that could bring the phenomenon to the fore of the concerned stakeholders and policy makers. Objective: To assess the prevalence of vitamin D deficiency among children in Kaliakoir Upazila, Gazipur District, Bangladesh. Materials and Methods: A cross-sectional study was conducted in children aged 0 month to <18 years attending Upazila Health (pediatrics) Complex and community clinics with minor illness. After obtaining informed written consent, venous blood was taken and serum 25(OH) D levels were determined by direct enzyme linked immunosorbent assay. Serum 25(OH) D was categorized as deficient (<10 ng/mL), insufficient (10–29 ng/mL) and sufficient (30–100 ng/mL). Results: Deficient serum 25(OH) D level was found in 30.15% infants of up to one year age group, 35% in 2–5 years, 35.21% in 6–11 years and 37.21% in 12–16 years age group. Insufficient level was found in 52.38% in infants up to one year, 50% in 2–5 years, 54.93% in 6–11 years and 59.30% in 12–16 years age group. Conclusion: The prevalence of vitamin D deficiency and insufficiency among children in rural Bangladesh is high. The study recommends that vitamin D supplementation in rural Bangladeshi children should be formally launched from first day of birth up to minimum adolescence. J Enam Med Col 2020; 10(2): 93-98